Analysis Of The Effectiveness Of LMWH Compared To UFH In COVID-19 Patients With Coagulation Disorders At Pasar Minggu Regional General Hospital - Edwina Dharmawati; Yusi Anggriani; Muhammad Reza (SEAN Institute, 2024)
Background: COVID-19 disease causes multiorgan damage and impacts the cardiovascular system. The Increase in death cases occurs due to coagulation disorders characterized by increased d-dimer parameters, bleeding, thrombocytopenia, and thrombosis. Objective: To analyze the effectiveness of the use of LMWH anticoagulants compared to UFH in COVID-19 patients with coagulation disorders in hospital. Methods: Observational retrospective data collected1with cross sectional design. Methods of collecting data on COVID-19 inpatients in the January-December 2021 period based on moderate, severe, and critical severity of the disease. The data used is medical record data and analysis using chi square. Results: The sample consisted of 6362patients who met the inclusion criteria with the largest difference in decrease D-dimer values in critical severity for LMWH (4.8 ug/ml) and UFH (4.0 ug/ml). Wilcoxon test analysis *showed that there was a significant difference between the use of LMWH and UFH based on the decrease in D-dimer values.